Noninvasive monitoring of deterioration in skeletal muscle function with forearm cast immobilization and the prevention of deterioration - Motobe, Mayuko (BioMed Central, 2004)
BACKGROUND: In this research inactivity was simulated by immobilizing the forearm region in a plaster cast. Changes in skeletal muscle oxidative function were measured using near-infrared spectroscopy (NIRS), and the preventative effect of the training protocol on deterioration of skeletal muscle and the clinical utility of NIRS were examined. METHODS: Fourteen healthy adult men underwent immobilization of the forearm of the non-dominant arm by plaster cast for 21 days. Eight healthy adult subjects were designated as the immobilization group (IMM) and six were designated as the immobilization + training group (IMM+TRN). Grip strength, forearm circumference and dynamic handgrip exercise endurance were measured before and after the 21-day immobilization period. Using NIRS, changes in oxidative function of skeletal muscles were also evaluated. Muscle oxygen consumption recovery was recorded after the completion of 60 seconds of 40% maximum voluntary contraction (MVC) dynamic handgrip exercise 1 repetition per 4 seconds and the recovery time constant (TcVO(2)mus) was calculated. RESULTS: TcVO(2)mus for the IMM was 59.7 ± 5.5 seconds (average ± standard error) before immobilization and lengthened significantly to 70.4 ± 5.4 seconds after immobilization (p < 0.05). For the IMM+TRN, TcVO(2)mus was 78.3 ± 6.2 seconds before immobilization and training and shortened significantly to 63.1 ± 5.6 seconds after immobilization and training (p < 0.05). CONCLUSIONS: The training program used in this experiment was effective in preventing declines in muscle oxidative function and endurance due to immobilization. The experimental results suggest that non-invasive monitoring of skeletal muscle function by NIRS would be possible in a clinical setting.